Test the Effectiveness of Bay Leaf Extract (Syzygium Polyanthum) in Lowering Uric Acid Levels in Male White Rats (Rattus Novergicus) - Lila Muliani; Gita Puspita; Rifka Anggraini Anggai (LPPM Universitas Bina Mandiri Gorontalo, 2021)
This study aims to determine whether there is a therapeutic effect on bay leaf extract (Syzygium polyanthum) in reducing uric acid levels in male white rats (Rattus novergicus) and to determine what dose of bay leaf extract (Syzyzgium polyanthum) is effective in reducing uric acid levels in male white rat (Rattus novergicus). The method in this study used Laboratory Experiments with Pretest-Posttest Control Group Design, the treatment groups were group I (negative control), group II (positive control), group III (bay leaf extract 0.4581 g), group IV (extract bay leaf 0.8181 g), and group V (bay leaf extract 1.1781 g). The results showed that bay leaf extract (Syzygium polyhantum) was positive for flavonoid compounds. Statistical data analysis by Kruskal Walis showed that 0.003 p significance value 0.005 means that there is a significant difference between uric acid levels before administration of bay leaf extract and uric acid levels after administration of bay leaf extract and continued with Duncan's analysis to see differences in effective doses.